When translation is not enough: Transcreation as a convention-defying practice. A practitioner's perspective - Benetello, Claudia (The Journal of Specialised Translation, 2018)
Despite common perceptions, transcreation is not glorified translation. Nor is it a synonym for 'creative translation' – a definition based on the questionable assumption that translation is not a creative act per se. While it is true that different types of texts allow for different degrees of freedom when it comes to 'transposing' them from one language to another, transcreation should be regarded as a different practice altogether. The typical translation evaluation grid used by professional reviewers contains several error categories. What happens when we apply this grid to transcreation? As it turns out, those errors can only apply to translation, not to transcreation, where they are not errors at all. Committing such errors, i.e. breaking the rules of grammar or spelling, is actually considered a plus in transcreation. Evidence suggests that transcreation is the only possible way to 'translate' marketing and advertising copy. In this article I draw on my professional experience as a copywriter involved in both origination and transcreation, and I will define transcreation as writing advertising or marketing copy for a specific market, starting from copy written in a source language, as if the target text had originated in the target language and culture. I also argue that creating target-language copy that can truly resonate with the target audience requires a special set of skills (language skills, copywriting skills, cultural sensitivity and local market understanding), which make the transcreation professional a fully-fledged consultant. I conclude on the specific skillset is required from transcreation professionals.